PICTURE AND PICTURE METHOD IN LEARNING MAHARAH KITABAH - Karimah, Binti; Setiyawan, Agung; Septianti, Alya Putri (STIQ Amuntai, 2024)
students. Teaching method is one of the ways used by educators in carrying out the learning process. The selection of inappropriate methods is an obstacle in achieving the learning objectives that have been found. Educators as much as possible should use methods that make the learning process interesting and also provide space for students to be creative. So that learning becomes very fun and not boring and can even improve students' maharah kitabah. The picture and picture model is a learning method that relies on images as media in the learning process. Pictures are one of the media that can help educators in the teaching process which makes learning more communicative and interesting, not even boring. The use of this media is designed so that students can analyze the picture into a brief description of what is in the picture. So that this method can be applied, of course, with the creativity of educators and make learning fun and interesting, especially in maharatul kitabah which most students have difficulty with.